2008
DOI: 10.1016/j.tibtech.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based antigen design: a strategy for next generation vaccines

Abstract: Vaccine design is progressing from empiricism towards the increasingly rational presentation of the targets of protective immunity. Nevertheless, most current vaccine antigens are essentially the native macromolecules of pathogens. These molecules are adapted to evade, not induce, immunity. High resolution structures reveal the electrostatic surfaces recognized by neutralizing antibodies and the architectures underlying these surfaces, thereby identifying which substructures must be left intact and which can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 69 publications
1
120
0
2
Order By: Relevance
“…The study by Connors et al identified a similarlylocated 37-kDa band as a degraded VP1 fragment, designated VP1*, which resulted from secondary thrombin proteolysis at Arg58 of VP1 . A similar digestion profile was observed for VP1-H3-H190-H190 (lane [4][5][6]. Three cleavage products were observed for the modular construct: (i) modular VP1 (bands at about 47 kDa; blue arrow), (ii) a GST tag (bands at about 25 kDa; orange arrow), and (iii) a cleavage product, which was represented as bands at approximately 39 kDa (green arrow).…”
Section: Sds-pagesupporting
confidence: 66%
See 3 more Smart Citations
“…The study by Connors et al identified a similarlylocated 37-kDa band as a degraded VP1 fragment, designated VP1*, which resulted from secondary thrombin proteolysis at Arg58 of VP1 . A similar digestion profile was observed for VP1-H3-H190-H190 (lane [4][5][6]. Three cleavage products were observed for the modular construct: (i) modular VP1 (bands at about 47 kDa; blue arrow), (ii) a GST tag (bands at about 25 kDa; orange arrow), and (iii) a cleavage product, which was represented as bands at approximately 39 kDa (green arrow).…”
Section: Sds-pagesupporting
confidence: 66%
“…Furthermore, the SDS-PAGE analysis showed that a small proportion of the 70-kDa contaminant (orange arrow) was detected in the earlier fractions of the eluted peak, which were fractions F1-F3 (lanes [4][5][6]. The proportion of the 70-kDa contaminant was considerably smaller than the proportion of the contaminant in the SEC-purified (lane 1)…”
Section: In Bed Modementioning
confidence: 96%
See 2 more Smart Citations
“…This approach to vaccination has been termed "rational" or "structural" vaccination since the 89 . In the case of anthrax, PA requires optimization for improved storage and a well-defined vaccine product that elicits longer-lasting immunity with fewer doses.…”
Section: Rationally Designed Vaccinesmentioning
confidence: 99%